Microstructural evolution of an aged Ni-based superalloy under two-stage hot compression with different strain rates. (5th December 2016) - Li, Kuo-Kuo; Chen, Ming-Song; Lin, Y.C.; Yuan, Wu-Quan
Abstract: The microstructural evolution of an aged Ni-based superalloy under two-stage hot compressive deformation with different strain rates is investigated. In terms of strain rate, the hot compressive tests include two types: constant and stepped strain rates. For the first type, the strain rate remains constant during the whole hot compression, while for the second type, the hot compression process consists of two stages: I and II. Moreover, the strain rate of stage I (0.01, 0.1, and 1 s − 1 ) is larger than that of stage II (0.001 s − 1 ). It is found that the strain rate and strain of stage I greatly affect the microstructural evolution for the hot compressive deformation with stepped strain rates. In the tested strain rate and strain, both the dissolution rate of δ phase and the dynamic recrystallization (DRX) volume fraction increase with the decrease of strain rate or the increase of strain in stage I. Compared with the constant strain rate hot deformation, the stepped strain rates can obviously promote DRX behaviors and the dissolution of δ phase if the appropriate strain rate and strain of stage I are chosen. These findings can be directly applied in the practical industrial production of superalloy components. Graphical abstract: Highlights: Effects of stepped strain rates on the microstructural evolution are significant. The appropriate stepped strain rates can obviously promote DRX behaviors. DDRX is the primary nucleation mechanism under constant and stepped strain rates.